2019
DOI: 10.1021/acsabm.9b00699
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles on Nanoscale Silica Platelets (AgNP/NSP) and Nanoscale Silica Platelets (NSP) Inhibit the Development of Fusarium oxysporum f. sp. niveum

Abstract: Nanotechnology has attracted much attention recently because of its agricultural applications. In this study, we analyzed the ability of two potential nanomaterials (NMs), nanoscale silica platelets (NSP) and silver nanoparticles on nanoscale silica platelets (AgNP/NSP), to control Fusarium wilt [caused by Fusarium oxysporum f. sp. niveum (Fon)] disease in watermelon. Both AgNP/NSP and NSP significantly reduced Fon mycelial growth and spore viability. In addition, AgNP/NSP decreased the mycelium viability at c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Multistimulus-responsive smart supramolecular hydrogels with AgNPs coated on cytidine-5-monophosphate-capped β-FeOOH nanohybrids demonstrated activity against Candida albicans . AgNPs-silica plates functioned as a fungicide to control the growth of Fusarium oxysporum . The photocatalytic disinfection capacity of TiO 2 makes it more applicable in many fields; however, its indoor use is limited as it requires UV light for activation.…”
Section: Biomedical Applications Of Agnpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multistimulus-responsive smart supramolecular hydrogels with AgNPs coated on cytidine-5-monophosphate-capped β-FeOOH nanohybrids demonstrated activity against Candida albicans . AgNPs-silica plates functioned as a fungicide to control the growth of Fusarium oxysporum . The photocatalytic disinfection capacity of TiO 2 makes it more applicable in many fields; however, its indoor use is limited as it requires UV light for activation.…”
Section: Biomedical Applications Of Agnpsmentioning
confidence: 99%
“…303 AgNPs-silica plates functioned as a fungicide to control the growth of Fusarium oxysporum. 315 The photocatalytic disinfection capacity of TiO 2 makes it more applicable in many fields; however, its indoor use is limited as it requires UV light for activation. To counter this problem, surface-modified TiO 2 −Ag−CuO nanoclusters in core−shell studies in dark and light conditions effectively inhibited the growth, sporulation, and generation of droplets.…”
Section: ■ Biomedical Applications Of Agnpsmentioning
confidence: 99%
“…For example, Chang et al (2019) reported that the use of silver nanoparticles on nanoscale silica platelets (Ag NP/NSP) significantly decreased the mycelial mass of Fusarium, when compared to the Fusarium-infected control. 43 The antimicrobial effect of Cu-based NMs in this study was likely due to the release of metal ions, which could directly interact with microbial cell membranes and induce toxicity. Similarly, Znbased NMs inhibited fungal activity by affecting hyphal morphology and inducing ROS production.…”
Section: Dha Activity Of Fusariummentioning
confidence: 81%
“…The detection angle was 173 • . electrophoretic mobility (U E ) was determined using laser Doppler velocimetry (LDV), wherein Zeta potential was recalculated using Henry's equation (2). Samples were prepared analogously to the sample preparation procedure for measuring the diameter.…”
Section: Determination Of Nanoparticle Surface Chargementioning
confidence: 99%
“…Silver, for centuries, has been considered a miracle medicine to cure wounds and protect food from spoilage. The development of silver in nanometric form conceived as nanoparticles (Ag NPs) with a size smaller than 100 nm has set a new direction in microbiologically-active agents [ 1 , 2 ]. The positive biological aspect describes two different mechanisms of action (direct and indirect).…”
Section: Introductionmentioning
confidence: 99%